Detection of high‐grade cervical disease among women referred directly to colposcopy after a positive HPV screening test varies with age and cytology findings - Farnsworth, Annabelle; Roberts, Jennifer M.; Garland, Suzanne M.; Crescini, Joanne; Kaldor, John M.; Machalek, Dorothy A. (International journal of cancer, 2020)
Australia's new HPV‐based cervical screening program is based on an algorithm that incorporates reflex cytology to guide decisions about further follow‐up with colposcopy and, if indicated, biopsy. We reviewed results for 2300 women referred directly for colposcopy after their first positive HPV screening test, to determine the proportion that had underlying histological high‐grade abnormality (HGA). Overall, HGA was detected in 24.3% of women. Among HPV16/18 positive women, 18.0% had HGA, increasing from 6.6% among women with negative cytology to 79.7% among women with high‐grade squamous lesion or worse, or any glandular lesion on cytology (HSIL+; P‐trend < .001). For this latter group, the proportion with HGA was higher among HPV16/18 positive women than among those positive for other oncogenic types (68.8%; P = .029). Among women with ASC‐H cytology, 51.8% had HGA, with no difference between HPV groups (P = .314). In analyses by age‐groups, detection of HGA was highest, at 36.4%, among women younger than 35 years, then decreased significantly to 5.9%, among women aged 65 to 74 years (P‐trend < .001). The relationship of decreasing HGA detection with increasing age was strong for women with negative cytology, and those with ASC‐H cytology (P‐trend < .001 for each). For women with HSIL+ cytology, detection of HGA was high and stable, regardless of age (P‐trend = .211). This report describes the first follow‐up colposcopy findings in Australia's new HPV‐based cervical screening program. The results demonstrate the additional value of reflex cytology in managing HPV positive women and suggest that further refinement of the risk‐based algorithm to account for age may be warranted. What's new? Australia's new human papilloma virus (HPV)‐based cervical screening program relies on a risk‐based algorithm incorporating reflex cytology to guide decisions about follow‐up colposcopy. In this report of the first follow‐up colposcopy findings, nearly one in four women referred directly for colposcopy under the algorithm had an underlying histological high‐grade abnormality (HGA). Detection of HGA increased with increasing grade of reflex cytology, but there was a substantial reduction in HGA detection with increasing age. The results demonstrate the additional value of reflex cytology in managing HPV‐positive women and suggest that the risk‐based algorithm should be further refined to account for age.